2019
DOI: 10.3390/ijms20194828
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Markers for Early Detection of Elevated Breast Cancer Risk in Women

Abstract: This study suggests that two newly discovered variants in the MSH2 gene, which codes for a DNA mismatch repair (MMR) protein, can be associated with a high risk of breast cancer. While variants in the MSH2 gene are known to be linked with an elevated cancer risk, the MSH2 gene is not a part of the standard kit for testing patients for elevated breast cancer risk. Here we used the results of genetic testing of women diagnosed with breast cancer, but who did not have variants in BRCA1 and BRCA2 genes. Instead, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In the current study, we found one patient carrying MSH6 and BRCA1 PVs simultaneously and without any other personal or family history of cancer, while all the other MMR variants identified were VUSs. Since Wu B et al reported two MSH2 variants used to classify VUS are pathogenic mutations 36 . Therefore, these VUS should be investigated further in a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we found one patient carrying MSH6 and BRCA1 PVs simultaneously and without any other personal or family history of cancer, while all the other MMR variants identified were VUSs. Since Wu B et al reported two MSH2 variants used to classify VUS are pathogenic mutations 36 . Therefore, these VUS should be investigated further in a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since Wu B et al reported two MSH2 variants used to classify VUS are pathogenic mutations. 36 Therefore, these VUS should be investigated further in a large number of patients. A case of CDH1 PV was found in one female patient diagnosed with ILC at 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…DNA MMR Alterations in BrCa Alterations or different variants in DNA MMR genes are correlated with an elevated risk for BrCa development. A study group explored the role of specific MSH2 variants in women without BRCA1/BRCA2 gene mutations (20). They detected a combination of two mutations (p. Ala272Val and p. Met592Val) and designated them as potentially pathogenic in sub-groups of patients.…”
Section: Dna Mismatch Repair System (Dna Mmr): Landscape and Mechanismsmentioning
confidence: 99%
“…Besides, MSH2 mutations are found in patients with endometrial carcinoma and adenocarcinoma of the colon. Besides, MSH2 mutation carriers have an increased risk of breast cancer (BC) with or without a LS family history 45 . A homozygous G to A transition mutation in the invariant G of the intron 10 splice acceptor of the MSH2 gene is associated with leukemia and multiple cafe´-au-lait spots, a feature of neurofibromatosis type 1 46 .…”
Section: Mmr Gene Polymorphism and Cancermentioning
confidence: 99%